Comparison of PlanetScope and Sentinel-2 satellite observations in mapping small-scale forest fires - Pham Duc, Binh; Nguyen Manh, Hung; Lacava, Teodosio (Vietnam Journal of Earth Sciences, 2026)
This study evaluates the performance of multispectral optical sensors onboard PlanetScope (PS) and Sentinel-2 satellites in mapping burned areas resulting from a small forest fire that occurred on 21 March, 2025, in Nghiem Mountain, northern Vietnam. Cloud-free pre- and post-fire imagery acquired on the same dates (17 January and 12 May, 2025) were used to compute the difference Normalized Difference Vegetation Index (dNDVI) using Red and Near-Infrared surface reflectance. A threshold value (T = 0.10), selected after analyzing the dNDVI histograms, was applied to classify burned (dNDVI > T) and unburned regions (dNDVI ≤ T). Results showed a strong spatial correlation between dNDVI maps derived from both satellites (R = 0.97), although Sentinel-2 tends to yield slightly higher dNDVI values than PS satellites. The burned area estimated from PS was 20.622 ha, while Sentinel‑2 produced a similar estimate of 20.225 ha, a difference of less than 2% and in close agreement with the official damage assessment report (~20 ha). Most discrepancies occurred along fire boundaries, where mixed pixels and spectral heterogeneity are expected. Our results demonstrate the effectiveness of Sentinel-2 and PS satellite imagery for mapping burned areas from small-scale fires, which is essential for forest management. Despite several limitations, including dependence on clear-sky conditions and the lack of a ground-based validation dataset, the proposed approach provides a timely and cost-effective solution for wildfire mapping at small scales, particularly important in remote regions.